2019
DOI: 10.1111/pedi.12896
|View full text |Cite
|
Sign up to set email alerts
|

Increased body fat and reduced insulin sensitivity are associated with impaired endothelial function and subendocardial viability in healthy, non‐Hispanic white adolescents

Abstract: Background Cardiovascular disease has its origins in adolescents. Endothelial dysfunction, arterial stiffness, and decreased endocardial oxygen supply: demand ratios are early functional markers of cardiovascular risk. The goal of this study was to determine the relationships of these markers to physical, inflammatory, and metabolic markers in healthy non‐Hispanic, white adolescents. Methods Thirty‐four of the 75 subjects were female. Mean age was 15.0 ± 1.7 years and mean body mass index (BMI) was 22.0 ± 5.8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…AIx75 value decreased) with age and adiposity, while no consistent correlation was identified in terms of lipid and glucose profiles. This was not surprising since a previous study also observed null findings of AIx with any of glucose or lipid profiles in adolescents [ 38 ]. Except for body fat mass in students with obesity, where a significantly strong correlation was found.…”
Section: Discussionmentioning
confidence: 63%
“…AIx75 value decreased) with age and adiposity, while no consistent correlation was identified in terms of lipid and glucose profiles. This was not surprising since a previous study also observed null findings of AIx with any of glucose or lipid profiles in adolescents [ 38 ]. Except for body fat mass in students with obesity, where a significantly strong correlation was found.…”
Section: Discussionmentioning
confidence: 63%
“…SEVR has been investigated in individuals with obesity, and evolving evidence shows that SEVR is altered in children and adolescents with obesity, although the mechanism by which this effect is mediated has not been fully elucidated ( 16 , 37 ). Recent studies showed that SEVR was positively correlated with insulin sensitivity in both obese and lean adolescents, suggesting an important role of SEVR in early cardiovascular risk determination in children and adolescents ( 38 , 39 ). The results of the present study indicated that SEVR increased by approximately 53% in adolescents with obesity following a diet and exercise intervention program and that AIx75 was significantly decreased by approximately 22% after the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Tocci et al [43,44], demonstrated that overweight adolescent patients have reduced SEVR values compared to normal-weight patients, similar to their carotid-femoral pulse wave velocity and aortic systolic blood pressure. Other recent studies conclude that SEVR values decrease with increased number of metabolic syndrome elements (p = 0.005) [44] and are correlated with both IR and IS [45,46]. So, we could hypothesize that chemerin may be a biomarker for arterial stiffness and for the risk of microvascular coronary damage.…”
Section: Discussionmentioning
confidence: 75%